Referent tracking for Digital Rights Management. (10th September 2007) - Ceusters, Werner; Smith, Barry
Digital Rights Management (DRM) covers the description, identification, trading, protection, monitoring and tracking of all forms of rights over both tangible and intangible assets. The Digital Object Identifier (DOI) system provides a framework for the persistent identification of entities involved in this domain. Although the system has been very well designed to manage object identifiers, some important questions relating to the creation and assignment of identifiers are left open. The paradigm of a Referent Tracking System (RTS) recently advanced in the healthcare and life sciences environment is able to fill these gaps. This is demonstrated by pointing out inconsistencies in the existing DOI models and by showing how they can be corrected using an RTS.